Design e análises de mastros de bambu para aplicações estruturais - Fernando José da Silva (2014)
The present work shows the development of hybrid, composite and beam masts with bamboo bars of the species Phyllostachys pubescens and establishment of its limit states. Research has been done on the use of masts in architectural structures and their functioning, structures from the earliest to the latest architectural structures, using roofing membrane systems. The construction and experimental trials enabled the development of knowledge and techniques that allow the improvement of the construction processes and optimization of the proposed structural system. Obtained gains in efficiency to the second hybrid mast, due to the increased claim cables, crosses the rising arm and better distribution along the main bamboo bar. The Southwell diagram allowed to know the global buckling axial force (Euler load), initial imperfection of the system and increased security to the application load in the following testing. The procedures were successful testing for the various steps, logistics and controls activities, results and data with good accuracy. The composite mast with side bars with internal spacers interposed, secured with threaded steel bars showed great performance against the initial masts, as their next load capacity of 45 kN, with six meters long and lateral deflection of only 70 mm. However, it can be seen that the load limit was limited by the crushing of the spacer holes in the end of smaller diameter and wall thickness and the contact stresses which may be substituted by straight screws with threaded only at the ends, thus avoiding stress concentration. For parametric studies, seven types of bamboo with different diameters and wall thicknesses, and lengths of the order of two to six meters have been created. For questions about gap in bolts, the numerical models are stricter about 25% for bamboo structures, being perfectly acceptable. It was also observed that the PDelta unload curve did not show a consistent shape, and recorded plastic deformation occurred by stress concentration in the screw holes, relaxing the system. Thus, was analyzed the fluency of the mast of data and considerations for applications of this type in structures. The tests with masts beam, with lateral dimensions of 3600 and 5400 mm, and continuous soul six meters, showed the fairly predictable operation. Its manufacturing process is relatively easy, not piercing the wall of bamboo for the passage of screws, avoiding stress concentration, although consume more bars, bamboo is appropriate for the use of smaller diameter bamboo, such as of the species Phyllostachys aurea and Bambusa tuldoides. In all cases, the numerical modeling can monitor the behavior occurred during the experiment, with perfect fits, validating the results to generalize the results of subsequent calculations of new structures. It was concluded that the option of type of masts will depend of loading and cost benefit, beyond the aesthetic and architectural point of view with the use of bamboo, contemporary structural element, sustainable, enabling new application possibilities in structures of this type, favoring biodiversity, interacting Design and Engineering.